15-7p-16=7p+29-4p

Simple and best practice solution for 15-7p-16=7p+29-4p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15-7p-16=7p+29-4p equation:


Simplifying
15 + -7p + -16 = 7p + 29 + -4p

Reorder the terms:
15 + -16 + -7p = 7p + 29 + -4p

Combine like terms: 15 + -16 = -1
-1 + -7p = 7p + 29 + -4p

Reorder the terms:
-1 + -7p = 29 + 7p + -4p

Combine like terms: 7p + -4p = 3p
-1 + -7p = 29 + 3p

Solving
-1 + -7p = 29 + 3p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-3p' to each side of the equation.
-1 + -7p + -3p = 29 + 3p + -3p

Combine like terms: -7p + -3p = -10p
-1 + -10p = 29 + 3p + -3p

Combine like terms: 3p + -3p = 0
-1 + -10p = 29 + 0
-1 + -10p = 29

Add '1' to each side of the equation.
-1 + 1 + -10p = 29 + 1

Combine like terms: -1 + 1 = 0
0 + -10p = 29 + 1
-10p = 29 + 1

Combine like terms: 29 + 1 = 30
-10p = 30

Divide each side by '-10'.
p = -3

Simplifying
p = -3

See similar equations:

| 5/4+1/2 | | 4/7x=3/4 | | 3/8/9+8/3/4= | | 3x+6y-4z=11 | | 9/17-1/2 | | 2m^2+mn-3n^2=0 | | 9x-13=-3 | | 12m+12n= | | 3x-33=5+1x | | 2(x+3)+5(5x)=-48 | | 0.5x-7=2x-19 | | -(-2a+9b-5c)= | | 8/3/4+7/2/3= | | 20X^2-49X+25=0 | | 2x-(9x+9)=6-7x | | 3(2.1+x)=20.4 | | x=3/5y-2 | | 12(-2x+1)=-14(x+2)+40-10x | | Y=20X^2-49X+25 | | 6/1/3+5/5/6= | | .5t+.9(20-t)=13.6 | | 6-(p+1)=4(1-2p) | | 5t+9(200-10t)=136 | | 18=v/1.8 | | 9x+9-10x+4=8x-9x-5 | | (5/x)-(2/3)=(14/3x) | | 2l-12=10 | | 9x+3=3+9x | | 5/x-2/3=14/3x | | 2l-12=10.5 | | 3x^3=3993 | | 1/5/6+5/6/7= |

Equations solver categories